Laughing at Love: L.E.L. and the Embellishment of Eros - Montwieler, Katherine (Romanticism on the Net)

(untitled) (Université de Montréal, 2003)
AbstractIn Letitia Elizabeth Landon’s The Improvisatrice, the physical body of the book puns on the female body. The erotics of poetess poetry is anchored in the sensuality of "embellishments," including the elaborate chirographic renditions of the initials “L.E.L.” Landon capitalizes on by eroticizing / embellishing all kinds of writing already in circulation. Moreover, The Improvisatrice enacts a kind of viewing that L.E.L. wants readers to participate in as they read. The poem encourages readers to engage in an "onanistic poesaphilia," to witness and participate in thinly-veiled pornographic scenes of indulgence in poetic sensibility. Landon presumes that being entertained consists in reading about people writing erotically. L.E.L.'s heroines are less passive sentimental victims than the proponents of "safe sex," an eroticism that is both bookish and solitary.